Mapping Alteration Zones for Detection of Economic Minerals using Integrated Tools in District Lower Dir, Northwest Khyber Pakhtunkhwa, Pakistan - Nazir Ul Islam; Liu Lei; Said Mukhtar Ahmad; Imran Ullah (International Journal of Economic and Environment Geology)
The study area is the part of Lower Dir which is geographically situated in the NW of Khyber Pakhtunkhwa province, Pakistan. Geologically this area lies in the western part of the well-known Kohistan IslandArc. Itrepresents the best exposure to subduction-related island arc and has been regarded asthe prominent metallogenic belt thathosts a variety of various minerals. The area has experiencedvarious tectonic episodes in the past and alteredthe rock assemblages which developedthe huge potential of copper and other precious base metals. To detect and monitor thesealteration zones,remote sensing techniquescoupled with field observation were evaluated in the current study. Landsat-7, Landsat-8,and Sentinel-2Bimages were processed under the shelter of Principal component(Crosta technique) analysis to demarcate the separate alteration zones. It was confirmed from the resultsthat the signature of the mappedalteration zone reflectsthe ground truth observationof copper mineralization in the target area. Furthermore, remote sensing signatures were correlated with thepetrographic details which also confirmedthese alteration zones. Spectrometry of the selected samples also delineatesthe same signature which is best fitted with the remote sensing data. From our current analysis,we suggest that a principal component technique in termsof medium to high-resolution remote sensing data is more beneficial for mineral exploration